Effect of Site‐Neutral Payment Policy on Long‐Term Acute Care Hospital Use. Issue 11 (3rd October 2018) - Makam, Anil N.; Nguyen, Oanh Kieu; Kirby, Benjamin; Miller, Michael E.; Xuan, Lei; Halm, Ethan A.
Abstract : Objective: To assess the projected effect of the Centers for Medicare and Medicaid Services new site‐neutral payment policy, which aims to decrease unnecessary long‐term acute care hospital (LTACH) admissions by reducing reimbursements for less‐ill individuals by 2020. Design: Observational. Setting: National 5% Medicare data (2011–12). Measurements: We examined the proportion of site‐neutral LTACH admissions. Regional LTACH market supply was defined as LTACH beds per 100, 000 residents, categorized according to tertile. We conducted a hospital‐level analysis to compare the projected effect of site‐neutral payment on "propensity score" matched high‐ and low‐LTACH‐use hospitals. Results: Forty‐one percent of LTACH admissions would be subjected to site‐neutral payment. The proportion of site‐neutral admissions was large, varied considerably according to LTACH (median 40%, interquartile range 22–60%), and was only modestly greater with greater market supply (Pearson correlation coefficient=0.23, p<.001; coefficient of determination=0.10). The site‐neutral payment policy would affect 47% of admissions from the highest‐supply regions, versus 30% from the lowest‐supply regions (p<.001); and 43% from high‐use hospitals versus 36% from propensity score‐matched low‐use hospitals (p<.001). Conclusion: A considerable proportion of LTACH admissions will be subjected to lower site‐neutral payments. Although the policy will disproportionately affect high‐use regions and hospitals, it will also affect nearly one‐third of the current LTACH population from low‐use hospitals and regions. As such, the site‐neutral payment policy may limit LTACH access in existing LTAC‐scarce markets, with potential adverse implications for recovery of hospitalized older adults.J Am Geriatr Soc 66:2104–2111, 2018.